Antibacterial Activity of Silver Nanodispersions in Solutions of Different Molecular Weight Chitosans. Issue 6 (6th February 2023) - Urodkova, Ekaterina K.; Uryupina, Ol'ga Ya.; Zhavoronok, Elena S.; Grammatikova, Natalia E.; Kharitonova, Tatiana V.; Senchikhin, Ivan N.
Abstract: The results of the testing of silver nanoparticles (AgNPs) antibacterial activity obtained in aqua solutions of high molecular chitosan and oligochitosans at near‐physiological pH values are demonstrated. Aggregative stable AgNPs were synthesized in solutions of chitosans of average molecular weight of 6, 12 and 311 kDa. Nanodispersions were characterized by UV‐Vis and FTIR, SEM and TEM. AgNPs formation was confirmed by the presence of the surface plasmon resonance peak at nearly 425 nm in the extinction spectrum and TEM. The average size of approximately 40–90 nm was determined by DLS, electron microscopy and UV‐Vis. Minimal inhibitory concentrations were determined by microdilution in the Mueller‐Hinton broth method. The AgNPs dispersions exhibit a significant antibacterial effect toward both Gram‐positive and Gram‐negative bacteria strain (MIC values are of 1–8 μg/ml). The effect is little dependent on polymer molecular weight. A two‐stage Staphylococcus aureus growth suppression effect was found for the first time. Abstract : Aggregative stable AgNPs were synthesized in solutions of chitosans of average molecular weight of 6, 12 and 311 kDa. The formation of NPs was confirmed by UV‐visible spectroscopy, DLS, and SEM. The AgNPs dispersions exhibit a significant antibacterial effect toward both Gram‐positive and Gram‐negative bacteria tested (MIC values are of 1–8 μg/ml).